The retrospective analysis of the network of specially protected natural territories in the Republic of Tuva - Kuksin, Aleksandr N.; Putintsev, Nikolay I.; Kuksina, Dolaana K.; Archimaeva, Tatyana P. (The New Research of Tuva, 2025)
The article examines the history of the development of the network of specially protected natural areas (SPNAs) located within the territory of the Republic of Tuva. The sources for the study included documents from the National Archives of the Republic of Tuva, materials from state institutions managing SPNAs of the Republic of Tuva, documents published on the Internet, as well as the personal experience of the authors, who were directly involved in the establishment, management, and operation of these areas. Since 1958, the genesis of 53 SPNAs has been considered, among which 2 (3.8%) are state nature reserves, 5 (9.4%) are natural parks, 30 (56.6%) are state nature sanctuaries of regional significance, 15 (28.3%) are natural monuments of regional significance, and 1 (1.9%) is a natural monument of municipal significance. The analysis of the network’s development by decade revealed that the highest number of SPNAs was established during the periods 1971–1980 — 19 sites (36.5% of the total created in the region), and 1981–1990 — 20 sites (38.4%). In subsequent decades up to 2024, no more than 4 SPNAs were established per decade. As of August 1, 2024, 35 specially protected natural areas are operating under the management of the SPNAs Directorate of the Republic of Tuva, with a total area of 2,931.1 thousand hectares, representing 17.3% of the region’s territory. The network includes the following categories: state nature reserves, a natural park, state nature sanctuaries of regional significance, natural monuments of regional significance, and a natural monument of municipal significance. The process of expanding the SPNAs network continues.